Nilai Tambah Kakao Fermentasi pada Unit Usaha Produktif (UUP) Tunjung Sari Br. Cangkup, Ds. Pesagi, Kec. Penebel, Kab. Tabanan - I WAYAN ARI YASTIKA; I NYOMAN GEDE USTRIYANA; DEWA AYU SRI YUDHARI (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2013)
ABSTRACT Improved Analysis of Value Added Cocoa Fermentation In Business Units productive (UUP) TunjungSari The purposeof this study was to determine the cocoa fermentation process, the determination of the value-added processing and obstacles encountered in increasing the added value of cocoa fermentation in productive Business Unit (UUP) Tunjung Sari. The study was conducted in January 2012, located at the Banjar Cangkup, Pesagi Village, District Penebel, Tabanan regency. Location selected (purposive). Data collection methods used were observation, interview and documentation. Selecting respondents (purposive) based on the duties and responsibilities ofeach.The analysis method used isdescriptive analysis method. This studyis descriptive qualitative. The primary data obtained fromdirect observationan dinterviews, and secondary data obtained from the study of literature. Based on the survey results revealed that the cocoa fermentation process include:(1)the procurement of raw materials, (2)bean sorting, (3)fermentation, (4)drying, (5)packing and (6)of storage.The results showed that the fermentation of raw material purchase cocoain 2011 amounting to Rp1,207,205,000, while sales of Rp 2,062,775,000. The added value obtained from the fermentation of cocoa processing Rp 2628.3/kg with a margin of 28.79%. From the above results should be productive Business Unit(UUP) SariTunjung more attention to quality, taking into account theamount of processing. Keyword : analysis, value added, cocoa fermentation